Effects of sleep on the realization of complex plans. (10th January 2018) - Barner, Christine; Altgassen, Mareike; Born, Jan; Diekelmann, Susanne
Summary: Sleep consolidates newly encoded memories, particularly those memories that are relevant for future behaviour. This study explored whether sleep facilitates the successful execution of relatively complex plans in the future. We applied the Dresden Breakfast Task, in which subjects are instructed to prepare a virtual breakfast comprising several tasks (e.g. table‐setting, preparing eggs). After forming a detailed plan how to realize these tasks, the sleep group ( n = 17) spent a night of sleep at home, monitored by polysomnography, and the wake group ( n = 19) spent a normal day awake, monitored by actigraphy. After a 12‐h interval, all participants were asked to prepare the virtual breakfast. Contrary to our hypothesis, overall performance in breakfast preparation did not differ significantly between the sleep and wake groups. However, sleep participants performed better in one of six tasks, specifically the 'table‐setting' task ( P < 0.01), which was driven by higher scores in a subtask measuring the correct position of the tableware ( P < 0.01). Additional exploratory analyses revealed that a significant number of wake participants performed below the minimal score of the sleep group ( P < 0.01) and sleep participants achieved the maximal score in significantly more subtasks than wake participants (57% versus 27%; P = 0.018). Plan adherence, assessing how well participants adhered to their own previously developed plan, did not differ between the sleep and wake groups. These findings provide the first evidence that sleep may support some aspects of the realization of complex, somewhat naturalistic plans.